2011
DOI: 10.1371/journal.pone.0027205
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of hsp70 Cluster in Camel (Camelus dromedarius) and Other Mammals

Abstract: Heat shock protein 70 (Hsp70) is a molecular chaperone providing tolerance to heat and other challenges at the cellular and organismal levels. We sequenced a genomic cluster containing three hsp70 family genes linked with major histocompatibility complex (MHC) class III region from an extremely heat tolerant animal, camel (Camelus dromedarius). Two hsp70 family genes comprising the cluster contain heat shock elements (HSEs), while the third gene lacks HSEs and should not be induced by heat shock. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…In Brown Swiss cattle, increased HSP72 or HSPA1A mRNA levels in peripheral blood mononuclear cells due to heat stress have also been reported by Lacetera et al (2006). Our results were also supported by earlier studies in camel showing that temperature elevation increases the level of constitutively expressed HSP70 in camel (Garbuz et al 2011;Ulmasov et al 1993).…”
Section: Discussionsupporting
confidence: 91%
“…In Brown Swiss cattle, increased HSP72 or HSPA1A mRNA levels in peripheral blood mononuclear cells due to heat stress have also been reported by Lacetera et al (2006). Our results were also supported by earlier studies in camel showing that temperature elevation increases the level of constitutively expressed HSP70 in camel (Garbuz et al 2011;Ulmasov et al 1993).…”
Section: Discussionsupporting
confidence: 91%
“…In Hydra oligactis , the transcription of HSP70 can be induced by high temperature, but rapid degradation of HSP70 mRNA at elevated temperature negates this increase in transcription 93 . In other cases, hints about changes in the regulation of the canonical HSPs can be found in the arrangement of heat shock elements in their promoter regions 94, 95 or from the (re)arrangement of HSP genes within the genome that suggest that they are differentially responsive to stimuli 96 .…”
Section: Evolution Of the Proteostasis Networkmentioning
confidence: 99%
“…It was also shown that the total protein synthesis in camel cells is significantly more resistant to heat than that of human cells [ 18 ]. Recently, inducible and constitutive camel HSP70 genes have been sequenced in our laboratory and compared with orthologous genes from other mammalian species [ 19 ]. Herein, we compare the transcriptional activity of the camel and human HSP70 gene promoters by exploring a luciferase reporter in an in vitro assay in two different human cell lines.…”
Section: Introductionmentioning
confidence: 99%